Trends and Dynamics of Popular Culture and Media Messages on Public Transport Literature in Nigeria - Eric Msughter Aondover; Omolara Akin-Odukoya (Lakhomi Journal Scientific Journal of Culture, 2024)
The study of popular culture and media messages on public transport in Nigeria reveals an intriguing intersection between mass communication, social behavior, and the broader cultural dynamics of the country. Public transport systems in Nigeria, ranging from buses (Danfo), taxis, to larger interstate vehicles (like the ones operated by companies such as Peace Mass Transit), serve as crucial spaces where various media messages, social trends, and cultural practices converge. The development of cars has radically transformed and revolutionized road transport system and affected the medium, channel, pattern and direction of mass communication, especially in Africa, Asia, North America, and South America where public transport vehicles are used as channels of advertisement, cultural communication, identity construction, and social reflection. This paper utilised secondary data to interrogate the trends and dynamics of popular culture and media messages on public transport literature in Nigeria. The paper adopted the Cultural Populism Theory. The theory represents activists’ opposition to the ways in which dominant forces in capitalist society shape people’s behaviour and ways of thinking. The literature on the trends and dynamics of popular culture and media messages on public transport in Nigeria demonstrates the importance of this seemingly mundane space as a site of cultural production, socialization, and political discourse.